Eq A Sketch 360, a Serious Toy for Drawing Equirectangular Spherical Perspectives - Araújo, António (2020)
Eq a Sketch 360 is a simple program for raster sketching VR panoramas in equirectangular spherical perspective. It is built as a serious toy, to develop sketching intuition regarding equirectangular drawing as proper perspective drawing, with its specific constructions of vanishing points, geodesics, line projections, antipodes, and grids. It is useful as a teaching aid and as a production tool for preliminary perspective sketches to be further rendered with other digital or traditional tools. It is naturally adapted for the input variables adequate for observational sketches. In this paper we survey the operation and purposes of the program. We also show how it calculates the equirectangular geodesic through two given points, which enables one of its main drawing features.